GAME EDUKASI MATEMATIKA UNTUK MENINGKATKAN PENALARAN SISWA BERBASIS ANDROID - Tholib, Abu; Eliyanto, Andik Elfandiyono; Supriadi, Ahmad; Syafiih, M; Rahman, M Fadhilur; Halimi, Ahmad (Insand Comtech : Information Science and Computer Technology Journal, 2024)
One of the subjects taught at every level of education is mathematics. Mathematics is an absolute science that cannot be revised but student interest in mathematics is declining because mathematics is considered a difficult subject for students and the media used is only books so that students get bored in learning. A new innovation is needed to increase student interest by utilizing technology, namely mathematics educational games. Educational games aim to increase students' interest as well as make learning fun by playing while learning. The research method used is the ADDIE Model, namely Analysis, Design, Development, Implementation and Evaluation. The result of this study is the Math Education Game on Android-Based Comparison Material based on the results of the blackbox test, it was found that all functions in the game ran according to the expected results and the assessment with a Likert scale to students obtained a score of 85.7% with a very agreeable interpretation. Thus, it can be concluded that this Android-based math educational game application is suitable for use by students as an independent learning medium and can help increase student interest in learning